Pengaruh Pola Asuh Autoritatif terhadap Kemandirian Anak Usia 4-5 Tahun di TPA Siti Hajar - Siti Nur Azkiah I. Hulawa; Nurul Aini Mm. Sodik; Nuraini Mauke; Tiara Avrianti Pilo; Melia Frilia Pakaya (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to determine the effect of authoritative parenting on the independence of children aged 4-5 years. The ex-post facto method was used as the research method, with the population being all parents of TPA Siti Hajar who use authoritative parenting. The sample was determined using a total sampling technique with data collection using a questionnaire. Data analysis was conducted using normality tests and simple regression. The results showed that parents use an authoritative parenting style. Respondents always ask their children about their lessons at school (64.08%), listen to their children talk about their school situation (57.00%), and provide encouragement when their children start to be lazy about their homework (66.70%), with a level of independence in the fairly good category, with indicators of self-confidence (65.00%), being able to make their own choices (52.31%), being responsible (50.60%), and being easy to make friends (55.00%). Therefore, the conclusion that can be conveyed is that there is an influence of authoritative parenting on the independence of children aged 4-5 years with a percentage of 46.00%. This study aims to determine the effect of authoritative parenting on the independence of children aged 4-5 years. The ex-post facto method was used as the research method, with the population being all parents of TPA Siti Hajar who use authoritative parenting. The sample was determined using a total sampling technique with data collection using a questionnaire. Data analysis was conducted using normality tests and simple regression. The results showed that parents use an authoritative parenting style. Respondents always ask their children about their lessons at school (64.08%), listen to their children talk about their school situation (57.00%), and provide encouragement when their children start to be lazy about their homework (66.70%), with a level of independence in the fairly good category, with indicators of self-confidence (65.00%), being able to make their own choices (52.31%), being responsible (50.60%), and being easy to make friends (55.00%). Therefore, the conclusion that can be conveyed is that there is an influence of authoritative parenting on the independence of children aged 4-5 years with a percentage of 46.00%.